Information flow in brazilian food market: The influence of the 2008 financial crisis (Research, Society and Development, 2021)
Brazilian agribusiness is gaining more and more international prominence thanks to the relevant production and export of agricultural commodities, as well as the great potential for development that this economic sector has in the country. The subject has attracted the attention of several researchers because, as the export sector grows, prices of these commodities for domestic consumption tend to rise, affecting the price of other foods. Understanding the dynamics of the price relation between these products is, therefore, of great value in order to avoid that possible financial crises also lead to food crises such as that of 2008. In order to contribute in this sense, the prices behavior of soybean, sugar, coffee and live cattle were analyzed here, as they are agricultural commodities produced on a large scale and traded worldwide. The study was based on the prices registered between 01/1997 and 12/2019, at CEPEA/ESALQ/USP, considering the periods before (07/1997 - 06/2007) and after (07/2007 - 12/2019) the 2008 crisis. The technique of analysis used was the Transfer Entropy - TE, that serves to quantify the flow of information between pairs of time series, as well as to obtain the direction of that flow. The technique was then applied to each pair of time series considering the pre-crisis and post-crisis periods. Results showed that the crisis affected the direction of information transfer between the pairs sugar-cattle, sugar-soybean and cattle-soybean. The time series prices of coffee, in turn, transmitted information to the other commodities in both periods.